INNER CONFLICT AND THE SEARCH FOR MEANING IN LIFE: A HUMANISTIC ANALYSIS OF WUNI NOVEL BY ERSTA ANDANTINO** - Tri Puji Setyawati; Onok Yayang Pamungkas; Eko Suroso; Kuntoro (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to examine the dynamics of inner conflict and the search for meaning in life experienced by the character Jaka in the novel Wuni through a humanistic psychology approach. Inner conflict in the novel functions not merely as a narrative aesthetic element, but also as a representation of the character’s existential struggle in confronting social pressures, past trauma, and inherited cultural and spiritual values. This research employs a qualitative descriptive method using content analysis techniques applied to the novel text. The data consist of narrative units containing inner conflict and the search for meaning in life, which are systematically coded to enhance analytical validity. The findings indicate that Jaka’s inner conflict is closely related to his inability to fulfill fundamental psychological needs, such as safety, social acceptance, and self-esteem. These conflicts subsequently drive the character into a process of searching for meaning through inner reflection, spiritual experiences, and confrontation with ancestral heritage. This process ultimately leads Jaka toward self-acceptance and self-actualization, as conceptualized in humanistic psychological theory. The findings affirm that Wuni represents literature as a medium of human reflection that integrates psychological, cultural, and spiritual dimensions. This study is expected to enrich literary studies grounded in humanistic psychology and contribute to literature education oriented toward the development of humanistic values.